2021
DOI: 10.1021/acs.jpcc.0c08572
|View full text |Cite
|
Sign up to set email alerts
|

Green Fluorine-Free Synthesis of Hollow Rectangular Prism-like TiO2 Mesocrystals with Exposed {001} Facets for High-Performance Dye-Sensitized Solar Cells

Abstract: In this work, the hollow rectangular prism-like TiO 2 (HRP-TiO 2 ) mesocrystals with exposed {001} facets were synthesized via an in-situ hydrothermal process without introducing any additional hydrofluoric acid or fluoride-containing compounds. A double-layer structured photoanode based on HRP-TiO 2 mesocrystals (as the light scattering top layer) and TiO 2 nanocrystalline (TiO 2 -NC, as the underlayer) was constructed. The dye-sensitized solar cell (DSSC) based on the double-layer photoanode showed a remarka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…HNPs with superior properties exhibit great potential in catalysis, 11−23 batteries, 24−28 drug delivery, 29−32 and solar cells. 33 It is well known that the thermal stability of NPs is lower than that of the bulk due to their lower cohesive energy. 34 Moreover, it has been found that unsupported NPs have a tendency to agglomerate; therefore, catalytic activity is difficult.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HNPs with superior properties exhibit great potential in catalysis, 11−23 batteries, 24−28 drug delivery, 29−32 and solar cells. 33 It is well known that the thermal stability of NPs is lower than that of the bulk due to their lower cohesive energy. 34 Moreover, it has been found that unsupported NPs have a tendency to agglomerate; therefore, catalytic activity is difficult.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the last decade, yolk–shell nanoparticles (YSNPs) have received great attention due to their unique structures that make them suitable for many applications, including nanocatalysis, sensors, , batteries, and medicine. , In addition, recently, hollow nanoparticles (HNPs) have attracted wide attention. HNPs with superior properties exhibit great potential in catalysis, batteries, drug delivery, and solar cells …”
Section: Introductionmentioning
confidence: 99%
“…Dye-sensitized solar cells (DSSCs) can be applied to directly store solar energy by photoelectricity conversion and to further utilize it. , The optimization of each of the individual components in DSSCs has been widely reported, corresponding to the porous semiconductor TiO 2 film photoanode, , sensitized dye, electrolytes for redox mediation, and counter electrodes (CEs). The focus of all research on CEs is to identify Pt-free electrocatalytic materials to replace the traditional expensive Pt-based CE catalysts so as to maintain high power conversion efficiencies (PCEs) and further increase the cost effectiveness of CEs. Particularly, V and VIB group transition metal compounds (TMCs) have advantages of many varieties, such as easy synthesis, low cost, and high catalytic performance, and are ideal substitutes as Pt-free CEs for DSSCs. At present, the preparation of TMCs as CE catalysts is generally based on the valence state; according to the molar ratio, the raw materials are directly mixed to obtain individual pure crystal materials by solid-state sintering at high temperature, and the morphology, structure, and catalytic performance could be further adjusted by changing the synthesis conditions, doping, modification, or other means to improve the catalytic performance. , As the base of TMC catalysis, the main material of the catalyst has fixed composition and single configuration, which makes its electrocatalytic performance far behind the requirements of DSSCs for CEs . In addition, an extremely high temperature (≥600 °C) and long time (≥4 h) were required in the sintering process of the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…Dye-sensitized solar cells (DSSCs) can be applied to directly store solar energy by photoelectricity conversion and to further utilize it. 1,2 The optimization of each of the individual components in DSSCs has been widely reported, corresponding to the porous semiconductor TiO 2 film photoanode, 3,4 sensitized dye, 5−10 electrolytes for redox mediation, 11 and counter electrodes (CEs). 12−14 The focus of all research on CEs is to identify Pt-free electrocatalytic materials to replace the traditional expensive Pt-based CE catalysts so as to maintain high power conversion efficiencies (PCEs) and further increase the cost effectiveness of CEs.…”
Section: Introductionmentioning
confidence: 99%